2021
DOI: 10.1016/j.psychres.2020.113568
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of serum IL-1β and TNF-α are associated with an increased probability of major depressive disorder

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.Higher levels of serum IL-1β and TNF-α are associated with an increased probability of major depressive disorder ABSTRACT Major depressive disorder (MDD) is a serious psychiatric disorder but there are no reliable risk assessment tools for this condition. The actual reason for affecting depression is still controversial. It is assumed that the dysregulated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 52 publications
4
49
0
Order By: Relevance
“…The puncture site was also adequately sanitized and cleaned before sample collection. Immediately after blood collection, the routine procedures were completed and the samples were stored at -80˚C [25][26][27][28].…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…The puncture site was also adequately sanitized and cleaned before sample collection. Immediately after blood collection, the routine procedures were completed and the samples were stored at -80˚C [25][26][27][28].…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…Psoriasis increases the risk of mental disorders, including depression, anxiety and suicide [ 134 ]. In addition to the psychological stress caused by psoriasis, it has been reported that inflammatory cytokines are related to mood disorders, including elevated levels of cytokines, including TNF-a, IL-6 and IL-1 [ 135 , 136 ]. Anti-depressants reduce the central nervous system’s inflammatory response and the levels of inflammatory cytokines, such as FAE [ 135 , 137 ].…”
Section: Adiponectin and Psoriasis Comorbiditiesmentioning
confidence: 99%
“…Together with our enrichment in several immunologic signatures, our result indicated that MDD with insomnia is associated with a dysfunctional immune system. Accumulating evidence has suggested that MDD is linked to elevated proinflammatory cytokines such as IL-1, IL-6, tumor necrosis factor (TNF)-α, and chemokines [85][86][87][88]. Therefore, we hypothesized that IL-1 could be a link for the mechanism of MDD through BTN3A.…”
Section: Discussionmentioning
confidence: 99%